Lipoprotein Profile in Immunological Non-Responders PLHIV after Antiretroviral Therapy Initiation - Masip, Jenifer; Jorba, Rosa; López-Dupla, Miguel; Domingo, Pere; Pacheco, Yolanda María; García-Pardo, Graciano; Martínez, Esteban; Viladés, Consuelo; Veloso, Sergi; Alba, Verónica; Olona, Montserrat; Vidal, Francesc; et al. (International journal of molecular sciences, 2022)
Nuclear magnetic resonance (NMR)-based advanced lipoprotein tests have demonstrated that LDL and HDL particle numbers (LDL-P and HDL-P) are more powerful cardiovascular (CV) risk biomarkers than conventional cholesterol markers. Of interest, in people living with HIV (PLHIV), predictors of preclinical atherosclerosis and vascular dysfunction may be associated with impaired immune function. We previously stated that immunological non-responders (INR) were at higher CV risk than immunological responders (IR) before starting antiretroviral therapy (ART). Using Liposcale® tests, we characterized the lipoprotein profile from the same cohort of PLHIV at month 12 and month 36 after starting ART, intending to explore what happened with these indicators of CV risk during viral suppression. ART initiation dissipates the differences in lipoprotein-based CV risk markers between INR and IR, and only an increase in the number of HDL-P was found in INR + IR when compared to controls (p = 0.047). Interestingly, CD4+ T-cell counts negatively correlated with medium HDL-P concentrations at month 12 in all individuals (ρ = −0.335, p = 0.003). Longitudinal analyses showed an important increase in LDL-P and HDL-P at month 36 when compared to baseline values in both IR and INR. A proper balance between a proatherogenic and atherogenic environment may be related to the reconstitution of CD4+ T-cell count in PLHIV.